How do you simplify #(3times10^-1)(8times10^-5)#?

1 Answer
Apr 29, 2017

Answer:

See the solution process below:

Explanation:

First, rewrite the expression as:

#(3 xx 8)(10^-1 xx 10^-5) => 24 xx (10^-1 xx 10^-5)#

Next, use this rule of exponents to multiply the 10s terms:

#x^color(red)(a) xx x^color(blue)(b) = x^(color(red)(a) + color(blue)(b))#

#24 xx (10^color(red)(-1) xx 10^color(blue)(-5)) => 24 xx 10^(color(red)(-1) + color(blue)(-5)) => 24 xx 10^-6#

Or, to put the expression into correct scientific notation:

#2.4 xx 10^-5#